2023
DOI: 10.1111/apps.12471
|View full text |Cite
|
Sign up to set email alerts
|

Examining discrimination in asynchronous video interviews: Does cultural distance based on country‐of‐origin matter?

Abstract: We conducted two studies to investigate how cultural differences based on country of origin influence the selection process in an asynchronous video interview (AVI) context. We drew upon the GLOBE cultural value dimensions and individual measures of prejudice to examine if raters evaluate job applicants who are more culturally dissimilar to them more negatively than culturally similar applicants. Professionals with hiring experience from the United Kingdom were recruited via the Prolific platform and asked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 136 publications
0
3
0
Order By: Relevance
“…As such, applicants from various cultures present images of themselves considered to be ideal according to their cultural standards. Understanding how IM use differs within an AVI context, therefore, has similar implications to FTF interviews, where discrimination and subconscious biases related to cultural distance may be present (Arseneault & Roulin, 2023;Huffcutt et al, 2011;Manroop et al, 2013).…”
Section: Importance Of Im In Interviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, applicants from various cultures present images of themselves considered to be ideal according to their cultural standards. Understanding how IM use differs within an AVI context, therefore, has similar implications to FTF interviews, where discrimination and subconscious biases related to cultural distance may be present (Arseneault & Roulin, 2023;Huffcutt et al, 2011;Manroop et al, 2013).…”
Section: Importance Of Im In Interviewsmentioning
confidence: 99%
“…One German study (Basch et al, 2021) found no relationship for any form of IM, whereas a North-American one found a positive effect of honest IM but no effect for deceptive IM on interview performance ratings (Roulin et al, 2023). Yet, such studies did not include cross-cultural samples, which is relevant given that the cultural distance between interviewers and interviewees can significantly impact how performance evaluations are assigned (Arseneault & Roulin, 2023). Despite the likelihood of subjective evaluator biases and based on the overall IMperformance literature, we predict that interviewees using more honest IM tactics will (generally) be evaluated more positively.…”
Section: Im Use and Interview Performancementioning
confidence: 99%
“…For instance, while we slightly adapted Tsui et al, 1992). Further, Arseneault and Roulin (2023) showed that cultural differences between the interviewee and the evaluator could bias evaluations in AVIs. Of course, these potential negative effects could possibly be mitigated through the implementation of highly structured interviews and standardized processes (Levashina et al, 2014;McCarthy et al, 2010) and AVIs are usually structured interviews.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 99%